Immunomodulatory Activity of Purple Button Herb (Borreria laevis Lamk.) on Macrophage Phagocytosis - Prasetyo, Mulyadi; Yuliastri, Wa Ode; Pusmarani, Jasria; Saranani, Selpirahmawati; Handayani, Putri (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
Immunomodulators operate through various mechanisms, one of which involves enhancing phagocytic activity. The purple button herb (Borreria laevis Lamk.) is recognized for containing secondary metabolites that may function as immunomodulators; however, its influence on phagocytosis has not been previously assessed. Consequently, a study explored the immunomodulatory effects of distinct fractions of the purple button herb on macrophage phagocytosis in male mice. Over seven days, the mice were orally administered ethanolic extract, ethyl acetate, and n-hexane fractions of the purple button herb. On the eighth day, the subjects were infected with Staphylococcus aureus. After euthanization, intraperitoneal fluid was collected to analyze macrophage phagocytosis activity. The study's results suggested that the ethanolic extract, ethyl acetate, and n-hexane fractions of the purple button herb tended to enhance macrophage activity, with the n-hexane fraction achieving the highest phagocytosis rate of 84.7%. The corresponding p-value > 0.05 in the LSD test indicated no statistically significant difference when compared to the positive control. In conclusion, the n-hexane fraction of the purple button herb demonstrates potential as an immunostimulant by augmenting macrophage activity.